Comparing Quantitative Immunohistochemical Markers of Angiogenesis to Contrast‐Enhanced Subharmonic Imaging. (7th July 2016) - Gupta, Aditi; Forsberg, Mark A.; Dulin, Kelly; Jaffe, Samantha; Dave, Jaydev K.; Halldorsdottir, Valgerdur G.; Marshall, Andrew; Forsberg, Anya I.; Eisenbrey, John R.; Machado, Priscilla; Fox, Traci B.; Liu, Ji-Bin; et al.
Abstract : Objectives: Different methods for obtaining tumor neovascularity parameters based on immunohistochemical markers were compared to contrast‐enhanced subharmonic imaging (SHI). Methods: Eighty‐five athymic nude female rats were implanted with 5 × 10 6 breast cancer cells (MDA‐MB‐231) in the mammary fat pad. The contrast agent Definity (Lantheus Medical Imaging, North Billerica, MA) was injected, and SHI was performed using a modified Sonix RP scanner (Analogic Ultrasound, Richmond, British Columbia, Canada) with a L9‐4 linear array (transmitting/receiving frequencies, 8/4 MHz). Afterward, specimens were stained for endothelial cells (CD31), vascular endothelial growth factor (VEGF), and cyclooxygenase 2 (COX‐2). Tumor neovascularity was assessed in 4 different ways using a histomorphometry system (×100 magnification: (1) over the entire tumor; (2) in small sub–regions of interest (ROIs); (3) in the tumor periphery and centrally; and (4) in 3 regions of maximum marker expression (so‐called hot spots). Results from specimens and from SHI were compared by linear regression. Results: Fifty‐four rats (64%) showed tumor growth, and 38 were successfully imaged. Subharmonic imaging depicted the tortuous morphologic characteristics of tumor neovessels and delineated small areas of necrosis. The immunohistochemical markers did not correlate with SHI measures over the entire tumor area or over small sub‐ROIs ( P > .18). However, when the specimens were subdivided into central and peripheral regions, COX‐2 and VEGF correlated with SHI in the periphery ( r = −0.42; P = .005; and r = −0.32; P = .049, respectively). Conclusions: When comparing quantitative contrast measures of tumor neovascularity to immunohistochemical markers of angiogenesis in xenograft models, ROIs corresponding to the biologically active region should be used to account for tumor heterogeneity.